227k views
0 votes
Solution of 4 |2y-3| -1 =11 step by step

User Mafor
by
5.7k points

1 Answer

3 votes

Answer:

y = 0, 3

Explanation:

1) Add 1 to both sides.

4 ∣ 2y −3 ∣ = 11 + 1

2) Simplify 11+1 to 12.

4 ∣ 2y − 3∣ = 12

3) Divide both sides by 4.

∣ 2y − 3∣ =​​ 12 / 4

4) Simplify 12/4 to 3.

∣ 2y − 3 ∣ = 3

5) Break down the problem into these 2 equations.

2y − 3 = 3

-(2y - 3 ) - 3

6) Solve the 1st equation: 2y − 3 = 3

y = 3

7) Solve the 2nd equation: -(2y - 3 ) - 3

y = 0

8) Collect all solutions.

y = 0, 3

User Bstampe
by
4.8k points